2013
DOI: 10.1038/cddis.2013.490
|View full text |Cite
|
Sign up to set email alerts
|

Placenta-derived mesenchymal stem cells improve memory dysfunction in an Aβ1–42-infused mouse model of Alzheimer’s disease

Abstract: Mesenchymal stem cells (MSCs) promote functional recoveries in pathological experimental models of central nervous system (CNS) and are currently being tested in clinical trials for neurological disorders, but preventive mechanisms of placenta-derived MSCs (PD-MSCs) for Alzheimer's disease are poorly understood. Herein, we investigated the inhibitory effect of PD-MSCs on neuronal cell death and memory impairment in Aβ1–42-infused mice. After intracerebroventrical (ICV) infusion of Aβ1–42 for 14 days, the cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(76 citation statements)
references
References 60 publications
5
70
0
1
Order By: Relevance
“…The challenging nature of stem cell therapy for AD is described in several excellent review papers published in recent years [137,138] . Despite these obstacles, numerous studies have demonstrated improvements in learning and memory by transplanting neural stem cells to the brains of rodents modeling AD [139][140][141][142][143][144][145][146][147][148] . In addition, transplantation of adipose-derived stem cells to mouse models of AD have shown restoration of memory deficits [149][150][151] and human umbilical cord-derived MSCs that have been differentiated to neuron-like cells also improve cognitive function in AD mouse models [152,153] .…”
Section: Stem Cell Transplantation For Neurological Disordersmentioning
confidence: 99%
“…The challenging nature of stem cell therapy for AD is described in several excellent review papers published in recent years [137,138] . Despite these obstacles, numerous studies have demonstrated improvements in learning and memory by transplanting neural stem cells to the brains of rodents modeling AD [139][140][141][142][143][144][145][146][147][148] . In addition, transplantation of adipose-derived stem cells to mouse models of AD have shown restoration of memory deficits [149][150][151] and human umbilical cord-derived MSCs that have been differentiated to neuron-like cells also improve cognitive function in AD mouse models [152,153] .…”
Section: Stem Cell Transplantation For Neurological Disordersmentioning
confidence: 99%
“…The hippocampal CA1 area was removed for further analysis of the protein expression of mTOR and downstream pathways and the levels of PICs. As previously reported by others [9, 10], in our present study αβ 1-42 was infused unilaterally via the ICV. It is noted that we did not observe significant differences in expression of mTOR and its downstream pathways between the right and left sides of the CA1 region in our preliminary experiments.…”
Section: Methodsmentioning
confidence: 56%
“…MSCs have been used to treat various CNS disorders in preclinical and clinical studies, such as spinal cord and traumatic brain injury [116][117][118] , ischemic stroke [31,40,56,62,69,97,[119][120][121][122][123] , intracranial hemorrhage (ICH) [124] , Parkinson's disease [125,126] , multiple sclerosis [127] , experimental autoimmune encephalomyelitis (EAE) [47,128,129] , amyotrophic lateral sclerosis [130,131] , Alzheimer's disease [132] , Huntington's disease [133][134][135] , and so on. Potential repair mechanisms involve transdifferentiation to replace damaged neural cells and production of growth factors by MSCs.…”
Section: Methods To Promote the Homing Of Mscs In The Treatment Of Cnmentioning
confidence: 99%